Potential carcinogenic erionite from Lessini Mounts, NE Italy: Morphological, mineralogical and chemical characterization. Issue 18 (16th September 2016) - Giordani, Matteo; Mattioli, Michele; Dogan, Meral; Dogan, Ahmet Umran
ABSTRACT: Exposure of humans to erionite fibers of suitable morphology and dimension has been unambiguously linked to the occurrence of malignant mesothelioma. For this reason, a morphological, morphometrical, mineralogical, and chemical investigation was performed on two representative samples of potential carcinogenic, fibrous erionite from Lessini Mounts, northeastern (NE) Italy, which has not apparently been examined previously. The first sample is erionite-Ca with an extremely ﬁbrous, hair-like and flexible appearance, and growth in intimate association with levyne. The second sample is erionite-Ca with prismatic to acicular crystals and rigid behavior, enriched in K + and Ca 2+ extra-framework cations. Although erionite is a nominally Fe-free phase, iron (Fe) was detected in low amounts in all the analyzed crystals. In both the investigated samples, erionite is present as individual fibers of respirable size. Considering that the toxicity and carcinogenic potential of erionite is associated with its size parameters, together with its in vivo durability and high surface area, most of the investigated fibers may also be potentially carcinogenic. The presence of erionite in extensively quarried and largely employed volcanic rocks, suggesting the need for detailed health-based studies in the region.